Pengaruh Supervisi Akademik dan Budaya Organisasi terhadap Mutu Sekolah Menengah Pertama Negeri Sub Rayon 4 Kabupaten Kendal - Sariyati, Sariyati; Miyono, Noor; Haryati, Titik (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Abstract This study aims to (1) know the effect of academic supervision on school quality, (2) know the effect of organizational culture on school quality, and (3) know the effect of academic supervision and organizational culture on school quality. This research approach uses a quantitative approach with a Proportional Stratified Random Sampling technique. Data collection method used is the questionnaire method. Data analysis using simple linear regression and multiple regression. From the research results it is known that (1) there is an effect of academic supervision on school quality of 62.6% with the following regression equation: Ŷ = 28.996 + 0.309 X1. (2) There is an influence of organizational culture on school quality of 6.19% with the following regression equation: Ŷ = 36.674 + 0.680 X2. (3) There is an influence of academic supervision and organizational culture together on school quality of 64.4% with a positive regression coefficient Ŷ = 46.671 + 0.615 X1 + 0.523 X2.